1999
DOI: 10.1086/209563
|View full text |Cite
|
Sign up to set email alerts
|

Heart and Mind in Conflict: the Interplay of Affect and Cognition in Consumer Decision Making

Abstract: This article examines how consumer decision making is influenced by automatically evoked task-induced affect and by cognitions that are generated in a more controlled manner on exposure to alternatives in a choice task. Across two experiments respondents chose between two alternatives: one (chocolate cake) associated with more intense positive affect but less favorable cognitions, compared to a second (fruit salad) associated with less favorable affect but more favorable cognitions. Findings from the two exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
1,267
4
20

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,615 publications
(1,352 citation statements)
references
References 44 publications
61
1,267
4
20
Order By: Relevance
“…Taxing working memory reduces people's ability to keep their long-term goals in mind and has detrimental consequences for self-control ability (Hinson et al, 2003;Shiv & Fedorikhin, 1999;Ward & Mann, 2000). Conversely, taxing the response inhibition component of executive functioning increases response inhibition in unrelated domains, which has a positive effect on self-control ability.…”
Section: Implications For Executive Functioningmentioning
confidence: 99%
“…Taxing working memory reduces people's ability to keep their long-term goals in mind and has detrimental consequences for self-control ability (Hinson et al, 2003;Shiv & Fedorikhin, 1999;Ward & Mann, 2000). Conversely, taxing the response inhibition component of executive functioning increases response inhibition in unrelated domains, which has a positive effect on self-control ability.…”
Section: Implications For Executive Functioningmentioning
confidence: 99%
“…Sometimes, the striving for immediate gratification is related to the desire to behave in a hedonically pleasing manner (Rook, 1987;Shiv and Fedorikhin, 1999). Along these lines, it is assumed that only products that are hedonically pleasing can induce urges to consume impulsively.…”
Section: #1203mentioning
confidence: 99%
“…Similarly, food choices are influenced by the "pleasantness" associated with consuming the food (Berridge, 1996), and associating greater pleasure with high fat foods is related to higher body weight (Mela & Sacchetti, 1991). Other work has demonstrated that individuals have affective associations with alcohol and marijuana use (Simons & Carey, 1998), smoking (Trafimow & Sheeran, 1998), and food choices (Shiv & Fedorikhin, 1999).…”
Section: Affective Associations With Health Behaviorsmentioning
confidence: 99%